2016
DOI: 10.1002/ejic.201501220
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Oligosilsesquioxane Growth in the In Situ Water Production Sol–Gel Route: Dependence on Water Availability

Abstract: Thiol-functionalized nanobuilding blocks (NBBs) were synthesized from 3-mercaptopropyltrimethoxysilane by using the in situ water production (ISWP) process in which the water needed to hydrolyze the precursor was provided by means of an esterification reaction. In the present study the reaction between 1-propanol and chloroacetic acid was used. Whereas the growth of the Si oligomers was followed at room temperature and 100°C using 1D 29 Si and 2D 1 H-29 Si heteronuclear single quantum correlation (HSQC) NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
(79 reference statements)
1
25
0
Order By: Relevance
“…For instance, with the 3-mercaptopropylsilane derivatives HSCH 2 CH 2 CH 2 Si(OPr) x (OMe) y (OH) 3-(x+y) , Borovin et al have observed a high frequency shift of 1.26 AE 0.02 ppm for the replacement of a propoxy by a methoxy group, regardless of the extend of hydrolysis. High-frequency shifts in the range 0.9-0.6 ppm and 2.2-1.8 ppm were also observed for the hydrolysis of a methoxy and propoxy group, respectively (Borovin et al 2016b). An additional source of Si solution NMR spectra, with the T n chemical shift zones, for silsesquioxanes obtained by the ISWP sol-gel route from 3-mercaptopropyltrimethoxysilane, propanol, chloroacetic acid, and dibutyltin dilaurate (1:18:6:0.015) after different reaction times at 100 C (Borovin et al 2016b) high-frequency shifts is the reduction of the valence angles related to the formation of short strained cycles such as the 6-membered ones.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 89%
See 3 more Smart Citations
“…For instance, with the 3-mercaptopropylsilane derivatives HSCH 2 CH 2 CH 2 Si(OPr) x (OMe) y (OH) 3-(x+y) , Borovin et al have observed a high frequency shift of 1.26 AE 0.02 ppm for the replacement of a propoxy by a methoxy group, regardless of the extend of hydrolysis. High-frequency shifts in the range 0.9-0.6 ppm and 2.2-1.8 ppm were also observed for the hydrolysis of a methoxy and propoxy group, respectively (Borovin et al 2016b). An additional source of Si solution NMR spectra, with the T n chemical shift zones, for silsesquioxanes obtained by the ISWP sol-gel route from 3-mercaptopropyltrimethoxysilane, propanol, chloroacetic acid, and dibutyltin dilaurate (1:18:6:0.015) after different reaction times at 100 C (Borovin et al 2016b) high-frequency shifts is the reduction of the valence angles related to the formation of short strained cycles such as the 6-membered ones.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 89%
“…High-frequency shifts in the range 0.9-0.6 ppm and 2.2-1.8 ppm were also observed for the hydrolysis of a methoxy and propoxy group, respectively (Borovin et al 2016b). An additional source of Si solution NMR spectra, with the T n chemical shift zones, for silsesquioxanes obtained by the ISWP sol-gel route from 3-mercaptopropyltrimethoxysilane, propanol, chloroacetic acid, and dibutyltin dilaurate (1:18:6:0.015) after different reaction times at 100 C (Borovin et al 2016b) high-frequency shifts is the reduction of the valence angles related to the formation of short strained cycles such as the 6-membered ones. This last effect generally represents a variation of 2-4 ppm for T 2 species (Brunet 1998;Matejka et al 2000), but it can be stronger as shown by the 29 Si chemical shifts of [(c-C 6 H 11 )SiO 1.5 ] 6 and [(c-C 6 H 11 )SiO 1.5 ] 8 , which equal À56 and À69 ppm, respectively (Feher et al 1989;Bassindale et al 2003).…”
Section: Nuclear Magnetic Resonancementioning
confidence: 89%
See 2 more Smart Citations
“…The extent of hydrolysis–condensation in dependence on the kinetics of water production was assessed by time-dependent monitoring of the reactions, mainly through infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and gel permeation chromatography (GPC) analyses, demonstrating the ability to tune SSQs’ size and architecture by simply controlling the reaction duration. In particular, in the case of thiol-functionalized SSQs (SH-NBBs) [ 14 ], obtained by controlled hydrolysis-condensation of 3-mercaptopropyltrimethoxysilane (McPTMS) with chloroacetic acid (ClAAc) in 1-propanol solution at 100 °C ( Figure 1 a), the well-defined octakis (3-mercaptopropylsilsesquioxane) is the major species between 70 and 100 h reaction time; on the contrary, the ladder-like species appeared predominant for lower duration, according to 29 Si NMR spectroscopy [ 15 ]. However, the ISWP route is characterized by the occurrence of different reactions ( Figure 1 b,c), leading also to side products such as chloroacetic acid-derived compounds that cannot be completely removed from the SH-NBBs solution.…”
Section: Introductionmentioning
confidence: 99%